Understanding Dyslexia in Children through Human Development Theories - Thuraya Ahmed Al-Shidhani; Vinita Arora (Sultan Qaboos University Medical Journal, 2012)
Dyslexia is a specific learning disability that is neurological in origin, with an estimated overall worldwide prevalence of 5–10% of the population. It is characterised by difficulties in reading, accuracy, fluency, spelling and decoding abilities. The majority of publications reviewed indicated that screening is performed at the preschool level. Screening can also be conducted at birth or the first year of life. Understanding human development theory, for example, Piaget’s human development theory, may help determine at which stage of childhood development dyslexia is more detectable, and therefore guide the management of this disability. The objective of this review is to provide a brief and updated overview of dyslexia and its management in children through human development issues.